2013
DOI: 10.1111/bjd.12372
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with treatment among patients with psoriasis: a web-based survey study

Abstract: From the perspective of patients, biologic treatment is promising. To improve further the quality of psoriasis care, the effectiveness and convenience of topical therapies, the safety of systemic therapies, and doctors' communication skills need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 35 publications
(69 reference statements)
8
89
0
5
Order By: Relevance
“…High impact of the treatment modality on satisfaction scores and greatest satisfaction with biologicals were confirmed in regression models controlling for several confounding factors. These results are well in line with several other studies (2,11,12,14,(20)(21)(22) and may be attributed to the high efficacy, favourable risk-benefit profile and convenient application mode of biologicals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High impact of the treatment modality on satisfaction scores and greatest satisfaction with biologicals were confirmed in regression models controlling for several confounding factors. These results are well in line with several other studies (2,11,12,14,(20)(21)(22) and may be attributed to the high efficacy, favourable risk-benefit profile and convenient application mode of biologicals.…”
Section: Discussionsupporting
confidence: 91%
“…However, several recent studies showed higher satisfaction rates for biologicals than for other treatment modalities (10)(11)(12)(13)(14). Patients' satisfaction with and preferences for specific systemic antipsoriatic medications have only been compared in a few studies, sometimes with conflicting findings (8,11,15,16).…”
mentioning
confidence: 99%
“…Topical therapies for psoriasis are generally associated with poor treatment satisfaction, poor adherence due to low efficacy, treatment inconvenience, unsatisfactory cosmetic appearance of the medications, and undesired side effects with long term use. 1820,3133 Thus our data suggest that a decrease in prescription topical medication use may contribute to improvements in QoL associated with skin clearance.…”
Section: Discussionmentioning
confidence: 66%
“…We hypothesized that patients with clear skin would be more likely to report lower DLQI scores corresponding to lesser impact of their skin disease on QoL compared to patients with almost clear skin. Secondarily, especially since topical medication use has been associated with poor treatment satisfaction, 1820 we also aimed to assess the differences in prescription topical medication use in patients with clear versus almost clear skin.…”
Section: Introductionmentioning
confidence: 99%
“…The most important element contributing to this satisfaction is effectiveness of the administered therapy, which should be accompanied by good contact with medical personnel, active participation of the patient in taking therapeutic decisions, his/her sufficient knowledge of the disease, skin care methods and potential adverse effects of administered medication [2][3][4][5][6][7][8][9][10][11][12][13]. Studies of adult psoriasis patients confirm that there is a significant correlation between treatment satisfaction and satisfaction with life in general [14,15], self-perception and perception of the world [15], and the role of emotions in the way of the patient's acting and thinking [16]. Fulfillment of patients' preferences regarding the management of psoriasis improves their satisfaction with the therapy [14,16].…”
mentioning
confidence: 99%